Evaluation of satellite-retrieved evapotranspiration based on a nonparametric approach over an arid region. Issue 19 (1st October 2020) - Pan, Xin; You, Chaoshuai; Liu, Yuanbo; Shi, Chunxiang; Han, Shuai; Yang, Yingbao; Hu, Jia
ABSTRACT: Daily evapotranspiration (ET) controlled by latent energy (LE) is an important variable used in the study of hydrology, meteorology, and ecology. A constant solar radiation ratio approach was introduced to the LE retrieval algorithm based on a nonparametric ET approach to upscale instantaneous LE temporally. On the basis of the proposed algorithm, this study retrieved the daily and eight-day LE using Moderate-resolution Imaging Spectroradiometer (MODIS) and China Meteorological Administration Land Data Assimilation System products and evaluated the daily and eight-day LE retrieval by using the ground observations and MOD16 product in Zhangye City during 25 June to 15 September 2012. Results show that the temporal-spatial distribution of retrieved result was reliable. The retrieved daily/eight-day LE could capture the dynamic change of ground observations, whereas the MOD16 LE was invalid. The retrieved daily (eight-day) LE was underestimated at all four (two) sites, with bias, root mean square error, and R 2 of −7.9 to −2.2 W m −2 (approximately −5 W m −2 ), 19.8 to 39.0 W m −2 (approximately 10 W m −2 ), and 0.72 to 0.84 (approximately 0.9), respectively. The proposed approach showed more satisfactory performance than the triangle approach under clear sky condition. The eight-day LE retrieval was considerably better than MOD16 LE and had (no/slight) influence on MOD16 LE (eight-day retrieval). In addition, the accurate estimation of net radiation, soil heat flux, land surface temperature, and air temperature could aid in improving LE retrieval. Future studies would focus on the improvement of the retrieval algorithm, input accuracy, and residuals.